2018
DOI: 10.1177/1120672118815110
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of self-reported computer vision syndrome symptoms and its associated factors among university students

Abstract: Purpose: To determine the prevalence of symptoms of computer vision syndrome and to identify its associated factors. The secondary objective was to assess knowledge and practices related to preventing computer vision syndrome symptoms. Methods: The data for this cross-sectional study were collected through a self-administered questionnaire distributed to 713 female undergraduates studying business and medicine in Saudi Arabia. The questionnaire included computer vision syndrome validated symptoms and factors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
129
1
18

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(170 citation statements)
references
References 23 publications
22
129
1
18
Order By: Relevance
“…Among these symptoms neck pain was found to be most common (57%). This result was in line with the study by Tawil et al 24 82.2%. In the study by Logaraj et al 5 61% students reported neck and shoulder pain.…”
Section: Discussionsupporting
confidence: 94%
“…Among these symptoms neck pain was found to be most common (57%). This result was in line with the study by Tawil et al 24 82.2%. In the study by Logaraj et al 5 61% students reported neck and shoulder pain.…”
Section: Discussionsupporting
confidence: 94%
“…Yet in another similar study in Saudi Arabia, dry eyes were reported by 51.5% of university students, which is quite high as compared to ours (33.8%). 12 While in a Sialkot study it was very close(32%) to ours. On the contrary, straining of eyes was reported by 48% of Sialkot students, which was contrastingly higher in our students (70.8%).…”
Section: Discussion Ocular Symptomssupporting
confidence: 83%
“…11 A similar study on university students in Saudi Arabia revealed that headache was experienced by 66.5% of the students, resulting from computer usage of more than 5 hrs, which is in line with our findings for the same duration of computer usage. 12 Results were in concordance with the Sialkot study, where headache was most common symptom (80%), followed by backache (60%). 13 When it came to usage of protective measures like anti-glare screens, it was equally lacking i.e., 62.5 % of our and 79.2% of students in Jamaican study never bothered to use it.…”
Section: Extra-ocular Symptomssupporting
confidence: 87%
“…The study by Mowatt et al, 2 indicates that approximately 40% of students at a university in Jamaica used computers for more than 6 hours a day and that studying is the main reason for their use in 51.3% of cases. Two studies conducted amongst university students in Saudi Arabia reported disparate exposure data; while Al Rashidi et al, reported that 36.4% of students used a computer more than 4 hours a day, 4 Al Tawil et al, reported higher exposure, since approximately 50% of the students used computers more than 5 hours a day 5 . Other studies conducted at universities in Nepal, 6 Romania 7 and Malaysia, 3 reported that 6.7%, 25.5% and 26.2% of students, respectively, used VDTs more than 5 hours per day and that approximately 60% of students took regular breaks 3,6 .…”
Section: Introductionmentioning
confidence: 99%